Formulation And Characterization Of Copper Nanoparticles Gel Of Asteracantha Longifolia For Management Of Skin Disease - Gour, Ayush; Jain, Nilesh; Chaurasia, Sumit; Jain, Ruchi; Goswami, R.B (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and characterization of copper nanoparticle (CuNP) gels containing Asteracantha longifolia extract for the management of skin diseases. The hydroalcoholic extract of Asteracantha longifolia was prepared and characterized for its phytochemical content, revealing the presence of alkaloids, flavonoids, phenols, and tannins, which are known for their therapeutic effects, including anti-inflammatory, antioxidant, and antimicrobial activities. Copper nanoparticles were synthesized and incorporated into gel formulations, with formulation F3 showing the highest yield and entrapment efficiency. The optimized formulation (F3) exhibited a particle size of 38.85 nm and a zeta potential of -45.53 mV, ensuring good stability. In vitro drug release studies showed a controlled and sustained release of active compounds, with formulation GF2 releasing the amount of drug in sustain manner. The release kinetics of the gel formulations followed a zero-order model, indicating steady drug release. The formulations exhibited favorable physical characteristics, including good homogeneity, texture, and washability. These results suggest that copper nanoparticle gels with Asteracantha longifolia extract have great potential as an effective treatment for skin conditions, offering sustained therapeutic effects.